A caged nicotine with nanosecond range kinetics and visible light sensitivity - Filevich, Oscar (2010)
We report the synthesis, characterization and applications of a ruthenium-bipyridine based caged nicotine. The complex [Ru(bpy)2(nic)2]2+ (where bpy=2,2' bipyridine and nic=nicotine (3-[(2S)-1-methylpyrrolidin-2-yl] pyridine)) releases nicotine with a quantum yield Φ=0.23 upon irradiation with biologically harmless, blue (473nm) or green (532nm) light. The photolysis reaction is clean and very fast, with a time constant of 17ns. The synthesis is simple and the obtained compound is characterized by NMR, UV-Vis spectroscopy and cyclic voltametry. We find that this compound is active in biological systems, being able to elicit action potentials in leech neurons. © 2010 Elsevier Inc.